(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
Dermatophytosis (ringworm), an infection of the superficial keratinized structures of the skin and hair, is the most common contagious skin disease in cattle. It is a remarkable public and veterinary health problem reported from different parts of the world and causes great economic loss. A number of calves were simultaneously affected with this disease in the cattle farm of Bangladesh Livestock Research Institute (BLRI). So, this study was undertaken to develop a suitable treatment approach for controlling the disease in the herd. A total of 20 calves of Red Chittagong Cattle (RCC) were selected for the trial. All the experimental calves were divided into five groups namely – T0, T1, T2, T3 and T4. T0 group was kept as control and T1, T2, T3 and T4 groups were allowed for treatment. The drugs used for treatment were griseofulvin, streptomycin-penicillin, antihistaminic and vitamin AD3E in group T1; ivermectin, streptomycin-penicillin, antihistaminic and vitamin AD3E in T2; topical antifungal ointment, griseofulvin, streptomycin-penicillin, antihistaminic and vitamin AD3E in T3; and topical antifungal ointment, ivermectin, streptomycin-penicillin, antihistaminic and vitamin AD3E in group T4. No drug was used in T0 (control).The duration of the experiment was about one month. The fungal spores of Trichophyton spp., and Microsporum spp. were observed in the samples (skin scrapping) under microscope using 20% potassium hydroxide solution. All experimental calves were observed after 7 days to know the response of the treatment. On the basis of visual observation the result was recorded on day 14. All experimental calves were observed after 7 days to know the response of the treatment. On the basis of visual observation the result was recorded on day 14. Calves in control group remain same. Calves suffering from chronic dermatomycosis or dermatophytosis (ringworm) can be treated with topical antifungal ointment, griseofulvin tablet, streptonmycin-penicillin injection, antihistaminic injection and vitamin AD3E injection as per dosages used in this experiment. If the case is acute, topical antifungal ointment and griseofulvin tablet may be recommended as treatment measures. Vitamin AD3E may or may not be used in this case. Asian Australas. J. Biosci. Biotechnol. 2017, 2 (1), 132-135